Perceptions of professional esports players on performance-enhancing substances. Issue 4 (October 2022) - Schubert, Mathias; Eing, Felix; Könecke, Thomas
Highlights: Yearly title releases and constant updates of FIFA cause high performance pressure. Perceived illegitimacy of prescribed drugs. Widespread acceptance and legitimacy of energy drinks and the like. Perceived lack of serious anti-doping efforts in FIFA esports context. Need for more anti-doping educational work and further measures in FIFA . Abstract: Along with the rapid rise of esports across the globe, the esports industry is increasingly confronted with issues concerning governance, regulations and manipulations. Software-cheating, match-fixing as well as doping seem to be widespread phenomena within professional esports competitions. Addressing these issues is challenging due to complex and fragmented governance structures and the lack of any central steering authority. This study looks into doping and performance enhancement in particular. Based on semi-structured interviews with (n = 9) selected professional FIFA esports players, we explore their perceptions of the use of drugs and other (allegedly) performance-enhancing substances such as energy drinks and gaming boosters. The core findings that emerged out of the data are a high performance pressure related to FIFA competitions as perceived by players, an ambivalent perception towards the legitimacy of different forms of performance enhancement and a lack of anti-doping measures on the part of organisations involved. The study is among the first to explore the view of players as one of the key stakeholders in the esports ecosystem.